Design of Egg Incubator Based-Palm Oil in Bokonzi City (Sud Ubangi Province), Democratic Republic of the Congo - Philippe Ebuma Dongo; JB Zanyako Bosanza; Damas Boboy Manzongo; Benjamin Zoawe Gbolo; Amédée Kundana Gbatea; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
A trial was conducted in 2017 at the Higher Institute of Agronomic Studies (ISEA) in Bokonzi with the aim of setting up an egg incubator using palm oil-based combustion as an energy source to produce chicks. During 21 days of hen egg incubation in this tool, temperatures varied between 36.8 and 40°C with a minimum of 35.8°C (day eight) and a maximum of 40.5°C (day three and fifteen). Although the temperature values (40.5°C) are slightly high with consequences on egg hatchability, the range of temperatures recorded during this study is within the acceptable threshold previously outlined by other researchers for hen egg incubation. Thus, with the daily frequency of 3 to 4 egg turnings, the hatchability rate reached 75%. This result is consistent with the values previously obtained by other researchers, i.e. 65 to 75%.  In addition, in terms of production costs, the palm oil heated incubator proved to be superior, resulting in a 79.6% reduction in fuel costs compared to some types of oil heated incubators. This reflects a relative benefit of 875 Congolese Francs (or 0.53USD) per chick produced. This simple technology, using an available energy source, appears to be more adapted to the income of farmers and to the needs of rural communities where hydroelectric and thermal energy sources (oil and gas that produce heat energy) are not accessible at all.